Ultra-thin asphalt concrete
By superbranching the nanosilicon dioxide, co-modifying the asphalt with SBS, and surface modification and grafting of the ore powder, the problems of insufficient mechanical properties and poor compatibility of ultra-thin asphalt concrete are solved, and Excellent mechanical properties and the effect of reducing segregation phenomena.
Patent Information
- Application Number
- CN202411443273.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-16
AI Technical Summary
During the use of existing ultra-thin asphalt concrete, there are problems such as insufficient mechanical properties and poor compatibility of modified asphalt, which leads to serious segregation and affects its application effect.
Surface modification of nanosilica using epoxy silane and addition of branched polyethyleneimine and glycidyl methacrylate to form surface hyperbranched nanosilica, and matrix as a composite additive with SBS for matrix asphalt Co-modified, and the ore powder was subjected to aminosilane surface modification and phenylmethane diisocyanate surface grafting to prepare excellent modified ore powder, and finally form ultra-thin asphalt concrete with excellent mechanical properties.
It significantly improves the mechanical properties of ultra-thin asphalt concrete, reduces the separation phenomenon of modified asphalt, enhances the interface performance between asphalt and mineral powder, and improves the service life of the road surface.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt concrete, and in particular relates to ultra-thin asphalt concrete. Background Art
[0002] Ultra-thin asphalt concrete is a small-particle, multi-gravel asphalt mixture, which is mainly paved on the road surface affected by the initial disease, so as to form a very thin protective layer on its surface. The reinforcement and repair of the protective layer can greatly extend the service life of the road surface. However, the existing ultra-thin asphalt concrete still has certain disadvantages that limit its actual application effect. This is because ultra-thin asphalt concrete is mainly composed of asphalt, coarse aggregate, fine aggregate, mineral powder, etc., and asphalt is used as a binder. Its quality plays a decisive role in the mechanical properties of ultra-thin asphalt concrete. A large number of studies have shown that ordinary matrix asphalt is often not suitable for Ultra-thin asphalt concrete mostly needs to be modified to achieve higher quality and performance requirements. Among them, using SBS (styrene-butadiene-styrene block copolymer) to modify asphalt is one of the most widely used technical means. However, due to the large difference and poor compatibility between SBS and matrix asphalt, there will be segregation problems, especially after a period of placement and storage, the segregation is more serious. Therefore, its actual modification effect still has a lot of room for improvement. In addition, the biggest feature of ultra-thin asphalt concrete is its thin thickness, which inevitably brings about the problem of insufficient mechanical properties. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide an ultra-thin asphalt concrete. The present invention first uses epoxy silane to modify the surface of nano-silica, then adds branched polyethyleneimine, and forms a hyperbranched structure with an amino terminal through the action of epoxy groups and amino groups, and then adds glycidyl methacrylate, and continues to realize the conversion of the terminal from amino to double bond based on the action of epoxy groups and amino groups, thereby obtaining a surface hyperbranched nano-silica, which is compounded with sulfur as a composite auxiliary agent and co-modified with SBS on base asphalt to obtain modified asphalt. Finally, when the modified asphalt, coarse aggregate, fine aggregate, basalt fiber and modified mineral powder containing isocyanate groups obtained by sequentially surface modification with aminosilane and surface grafting with phenylmethane diisocyanate are used as components, the ultra-thin asphalt concrete formed has excellent mechanical properties after actual construction on the road surface.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] An ultra-thin asphalt concrete comprises 100 parts by weight of modified asphalt, 50-60 parts by weight of coarse aggregate, 20-25 parts by weight of fine aggregate, 15-20 parts by weight of modified mineral powder and 5-10 parts by weight of basalt fiber.
[0006] As a preferred technical solution of the present invention, the modified asphalt is prepared by the following steps:
[0007] 100 parts by weight of base asphalt are heat treated at 165-170°C for 10-15 minutes, then 5-7 parts by weight of styrene-butadiene-styrene block copolymer are added, stirred at a constant temperature for 20-30 minutes, then 2-3 parts by weight of composite additives are added, sheared at 175-180°C for 45-60 minutes, and finally grown at 160-165°C for 60-70 minutes to complete the preparation; the composite additive is a mixture of surface hyperbranched nano-silica and sulfur in a mass ratio of 1:0.3-0.4.
[0008] Furthermore, the shearing rotation speed is 4000-5000rpm.
[0009] Furthermore, the surface hyperbranched nano-silica is prepared by the following steps:
[0010] Step A: Add 1-2 parts by weight of nano-silica to 100 parts by weight of toluene, and then stir and mix at room temperature for 10-15 minutes in an ultrasonic wave with a power of 300-400 W, then add 1-1.5 parts by weight of epoxy silane, stir at 100-105° C. for 10-12 hours under a nitrogen atmosphere, filter, take the filter residue, wash it with acetone, and finally vacuum dry it at 40-70° C. until constant weight, to obtain epoxy nano-silica;
[0011] Step B: adding 2-3 parts by weight of epoxylated nano-silica to 100 parts by weight of 1,2-dichloroethane, and then stirring and mixing at room temperature for 10-15 minutes in an ultrasonic wave with a power of 300-400W, then adding dropwise 15-20 parts by weight of a branched polyethyleneimine solution at 50-60°C while stirring, and continuing to stir at a constant temperature for 4-6 hours after the dropwise addition is completed, filtering, taking the filter residue, washing it with anhydrous ethanol, and finally vacuum drying it at 40-70°C until constant weight, to obtain amino hyperbranched nano-silica;
[0012] Step C: Add 2-3 parts by weight of amino hyperbranched nano-silica and 4-5 parts by weight of glycidyl methacrylate to 100 parts by weight of dimethyl sulfoxide, then stir in the dark at 60-80° C. for 4-6 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 40-70° C. until constant weight, and the preparation is completed.
[0013] Preferably, the epoxysilane in step A is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0014] Preferably, the dripping rate in step B is controlled at 1-2 drops / s.
[0015] Preferably, the branched polyethyleneimine solution in step B refers to a mixture obtained by mixing branched polyethyleneimine 600 and 1,2-dichloroethane in a mass ratio of 1:5-7 at 50-60° C. with stirring for 30-60 min and then maintaining a constant temperature.
[0016] As a preferred technical solution of the present invention, the modified mineral powder is prepared by the following steps:
[0017] Step a: adding 5-8 parts by weight of deionized water, 2-3 parts by weight of mineral powder and 0.5-1 parts by weight of aminosilane to 100 parts by weight of anhydrous ethanol, stirring at 70-75° C. for 20-24 hours, filtering, taking the filter residue, washing it with anhydrous ethanol, and finally vacuum drying at 50-70° C. until constant weight, to obtain an amination mineral powder;
[0018] Step b: Add 2-3 parts by weight of amination ore powder and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 70-80°C for 1-2h, filter, take the filter residue, wash with N,N-dimethylformamide, and finally vacuum dry at 100-105°C until constant weight, and the preparation is completed.
[0019] Furthermore, the aminosilane in step a is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0020] A construction method for ultra-thin asphalt concrete, the construction method comprising the following steps:
[0021] Add coarse aggregate, fine aggregate, modified mineral powder and basalt fiber to the modified asphalt, then stir and mix at 155-160℃ for 20-30min, spread on the road surface, cool naturally to 90-95℃, roll and let stand for 3-5 days.
[0022] As a preferred technical solution of the present invention, the paving thickness is 2-2.5 cm.
[0023] As a preferred technical solution of the present invention, the rolling refers to rolling using a 10-12T roller.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention first uses epoxy silane to modify the surface of nano-silica, then adds branched polyethyleneimine, and forms a hyperbranched structure with an amino terminal through the action of epoxy groups and amino groups. Then, glycidyl methacrylate is added, and the end group is converted from amino to double bond based on the action of epoxy groups and amino groups, thereby obtaining a surface hyperbranched nano-silica, which is then compounded with sulfur as a composite auxiliary agent and co-modified with SBS on base asphalt to obtain modified asphalt. Finally, when the modified asphalt, coarse aggregate, fine aggregate, basalt fiber and modified mineral powder containing isocyanate groups obtained by sequentially surface modification with aminosilane and surface grafting with phenylmethane diisocyanate are used as components, the ultra-thin asphalt concrete formed has excellent mechanical properties after being actually constructed on the road surface.
[0026] (2) Based on the problem of poor compatibility and easy segregation when using SBS to modify the base asphalt in the prior art, the present invention creatively prepares a surface hyperbranched nano-silica with double bonds as the terminal group, and mixes it with sulfur as a composite auxiliary agent to co-modify the base asphalt with SBS. On the one hand, sulfur, as a small molecule, can generate double-terminal free radicals at high temperature and has high activity. It can produce a certain cross-linking effect with SBS, greatly enhancing the network structure of the polymer, thereby inhibiting the segregation of the two phases, so that the mechanical properties of the final ultra-thin asphalt concrete are improved. On the other hand, the surface Hyperbranched nano-silica contains a large number of terminal double bonds, which can also participate in the actual cross-linking system. At the same time, due to the special structure of the hyperbranching itself, the sites are many and dense. Therefore, compared with ordinary discrete double bonds, it can also greatly promote the internal friction of the internal molecular structure of asphalt. Ultimately, it not only improves the segregation problem to a certain extent, but also greatly improves the mechanical properties. In addition, nano-silica, as a commonly used reinforcing particle, can be better dispersed and filled in the entire ultra-thin asphalt concrete system after surface hyperbranching modification, thereby better playing a reinforcing role.
[0027] (3) The present invention is based on the fact that asphalt in ultra-thin asphalt concrete will be adsorbed on the surface of mineral powder to form a thin film, thereby producing an excellent adhesion effect with coarse / fine aggregates. To this end, the mineral powder is specifically surface-modified with aminosilane and surface-grafted with phenylmethane diisocyanate in sequence, thereby preparing a modified mineral powder containing isocyanate groups on the surface. The extremely high activity of the isocyanate group allows it to produce a strong interaction with the groups in the modified asphalt, thereby greatly improving the interfacial performance between the two. Ultimately, the mechanical properties of the ultra-thin asphalt concrete are further improved. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] The coarse aggregate in all the embodiments and comparative examples of the present invention is basalt, and the gradations include 9.5-13.2 mm, 4.75-9.5 mm and 2.36-4.75 mm, with a mass ratio of 1:27:2.5. The specific performance indicators are shown in Table 1.
[0030] The fine aggregates are all limestone, and the gradations include 1.18-2.36mm, 0.6-1.18mm, 0.3-0.6mm, 0.15-0.3mm and 0.075-0.15mm. The mass ratio is 5:3:3:3:2. The specific performance indicators are shown in Table 2.
[0031] The specific performance indicators of mineral powder are shown in Table 3.
[0032] The matrix asphalt was purchased directly from Shandong Yingbang Asphalt Technology Co., Ltd., with the model number of 70# asphalt; the styrene-butadiene-styrene block copolymer was purchased directly from the market, from Baling Branch of China Petrochemical Corporation, with the brand number of YH-791; the nano-silicon dioxide was purchased directly from the market, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with the model number of XFI03; the basalt fibers were purchased directly from the market, from Jiangsu Jumao New Material Technology Co., Ltd., with the trade name of basalt fiber for asphalt mixture.
[0033] Table 1. Performance indicators of coarse aggregate
[0034]
[0035] Table 2. Performance indicators of fine aggregate
[0036]
[0037] Table 3. Performance indicators of mineral powder
[0038]
[0039] Example 1
[0040] An ultra-thin asphalt concrete comprises 100 parts by weight of modified asphalt, 50 parts by weight of coarse aggregate, 20 parts by weight of fine aggregate, 15 parts by weight of modified mineral powder and 5 parts by weight of basalt fiber.
[0041] The modified asphalt is prepared by the following steps:
[0042] 100 parts by weight of base asphalt are heat treated at 165°C for 10 minutes, then 5 parts by weight of styrene-butadiene-styrene block copolymer are added, stirred at a constant temperature for 20 minutes, then 2 parts by weight of a composite additive are added, sheared at 175°C for 45 minutes, and finally developed at 160°C for 60 minutes to complete the preparation; the composite additive is a mixture of surface hyperbranched nano-silica and sulfur in a mass ratio of 1:0.3.
[0043] The shearing rotation speed is 4000 rpm.
[0044] The surface hyperbranched nano-silica is prepared by the following steps:
[0045] Step A: add 1 part by weight of nano-silica to 100 parts by weight of toluene, and then stir and mix at room temperature for 10 minutes in an ultrasonic wave with a power of 300 W, then add 1 part by weight of epoxysilane, stir at 100° C. for 10 hours under a nitrogen atmosphere, filter, take the filter residue, wash it with acetone, and finally vacuum dry it at 40° C. until constant weight, to obtain epoxy nano-silica;
[0046] Step B: Add 2 parts by weight of epoxylated nano-silica to 100 parts by weight of 1,2-dichloroethane, and then stir and mix at room temperature for 10 minutes in an ultrasonic wave with a power of 300 W, then dropwise add 15 parts by weight of branched polyethyleneimine solution at 50° C. while stirring, continue to stir at constant temperature for 4 hours after the dropwise addition is completed, filter, take the filter residue, wash it with anhydrous ethanol, and finally vacuum dry it at 40° C. until constant weight, to obtain amino hyperbranched nano-silica;
[0047] Step C: Add 2 parts by weight of amino hyperbranched nano-silica and 4 parts by weight of glycidyl methacrylate to 100 parts by weight of dimethyl sulfoxide, then stir in the dark at 60° C. for 4 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 40° C. until constant weight, and the preparation is completed.
[0048] The epoxysilane in step A is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0049] The dropping rate in step B is controlled at 1 drop / s.
[0050] The branched polyethyleneimine solution in step B refers to a mixture obtained by mixing branched polyethyleneimine 600 and 1,2-dichloroethane in a mass ratio of 1:5 at 50° C. with stirring for 30 minutes and then maintaining a constant temperature.
[0051] The modified mineral powder is prepared by the following steps:
[0052] Step a: Add 5 parts by weight of deionized water, 2 parts by weight of mineral powder and 0.5 parts by weight of aminosilane to 100 parts by weight of anhydrous ethanol, then stir at 70° C. for 20 hours, filter, take the filter residue, wash with anhydrous ethanol, and finally vacuum dry at 50° C. until constant weight, to obtain an amination mineral powder;
[0053] Step b: Add 2 parts by weight of amination ore powder and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 70°C for 1 hour, filter, take the filter residue, wash it with N,N-dimethylformamide, and finally vacuum dry it at 100°C until constant weight, and the preparation is completed.
[0054] The aminosilane in step a is γ-aminopropyltrimethoxysilane.
[0055] A construction method for ultra-thin asphalt concrete, the construction method comprising the following steps:
[0056] Add coarse aggregate, fine aggregate, modified mineral powder and basalt fiber to the modified asphalt, then stir and mix at 155°C for 20 minutes, spread on the road surface, cool naturally to 90°C, roll and let stand for 3 days.
[0057] The paving thickness is 2 cm.
[0058] The rolling refers to rolling using a 10T roller.
[0059] Example 2
[0060] An ultra-thin asphalt concrete comprises 100 parts by weight of modified asphalt, 60 parts by weight of coarse aggregate, 25 parts by weight of fine aggregate, 20 parts by weight of modified mineral powder and 10 parts by weight of basalt fiber.
[0061] The modified asphalt is prepared by the following steps:
[0062] 100 parts by weight of base asphalt are heat treated at 170°C for 15 minutes, then 7 parts by weight of styrene-butadiene-styrene block copolymer are added, stirred at a constant temperature for 30 minutes, then 3 parts by weight of composite additives are added, sheared at 180°C for 60 minutes, and finally grown at 165°C for 70 minutes to complete the preparation; the composite additive is a mixture of surface hyperbranched nano-silica and sulfur in a mass ratio of 1:0.4.
[0063] The shearing rotation speed is 5000 rpm.
[0064] The surface hyperbranched nano-silica is prepared by the following steps:
[0065] Step A: Add 2 parts by weight of nano-silica to 100 parts by weight of toluene, and then stir and mix at room temperature for 15 minutes in an ultrasonic wave with a power of 400 W, then add 1.5 parts by weight of epoxysilane, stir at 105° C. for 12 hours under a nitrogen atmosphere, filter, take the filter residue, wash it with acetone, and finally vacuum dry it at 70° C. until constant weight, to obtain epoxy nano-silica;
[0066] Step B: Add 3 parts by weight of epoxylated nano-silica to 100 parts by weight of 1,2-dichloroethane, and then stir and mix at room temperature for 15 minutes in an ultrasonic wave with a power of 400 W, then dropwise add 20 parts by weight of branched polyethyleneimine solution at 60° C. while stirring, continue to stir at constant temperature for 6 hours after the dropwise addition is completed, filter, take the filter residue, wash it with anhydrous ethanol, and finally vacuum dry it at 70° C. until constant weight, to obtain amino hyperbranched nano-silica;
[0067] Step C: Add 3 parts by weight of amino hyperbranched nano-silica and 5 parts by weight of glycidyl methacrylate to 100 parts by weight of dimethyl sulfoxide, then stir in the dark at 80° C. for 6 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, and the preparation is completed.
[0068] The epoxysilane in step A is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0069] The dropping rate in step B is controlled at 2 drops / s.
[0070] The branched polyethyleneimine solution in step B refers to a mixture obtained by mixing branched polyethyleneimine 600 and 1,2-dichloroethane in a mass ratio of 1:7 at 60° C. with stirring for 60 minutes and then maintaining a constant temperature.
[0071] The modified mineral powder is prepared by the following steps:
[0072] Step a: adding 8 parts by weight of deionized water, 3 parts by weight of mineral powder and 1 part by weight of aminosilane to 100 parts by weight of anhydrous ethanol, stirring at 75° C. for 24 hours, filtering, taking the filter residue, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain an amination mineral powder;
[0073] Step b: Add 3 parts by weight of amination ore powder and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 80°C for 2h, filter, take the filter residue, wash with N,N-dimethylformamide, and finally vacuum dry at 105°C until constant weight, and the preparation is completed.
[0074] The aminosilane in step a is γ-aminopropyltrimethoxysilane.
[0075] A construction method for ultra-thin asphalt concrete, the construction method comprising the following steps:
[0076] Add coarse aggregate, fine aggregate, modified mineral powder and basalt fiber to the modified asphalt, then stir and mix at 160°C for 30 minutes, spread on the road surface, cool naturally to 95°C, roll, and let stand for 5 days.
[0077] The paving thickness is 2.5 cm.
[0078] The rolling refers to rolling using a 12T roller.
[0079] Example 3
[0080] An ultra-thin asphalt concrete comprises 100 parts by weight of modified asphalt, 55 parts by weight of coarse aggregate, 23 parts by weight of fine aggregate, 18 parts by weight of modified mineral powder and 8 parts by weight of basalt fiber.
[0081] The modified asphalt is prepared by the following steps:
[0082] 100 parts by weight of base asphalt are heat treated at 168°C for 13 minutes, then 6 parts by weight of styrene-butadiene-styrene block copolymer are added, stirred at a constant temperature for 25 minutes, then 2.5 parts by weight of composite additives are added, sheared at 178°C for 50 minutes, and finally developed at 163°C for 65 minutes to complete the preparation; the composite additive is a mixture of surface hyperbranched nano-silica and sulfur in a mass ratio of 1:0.35.
[0083] The shearing rotation speed is 4500 rpm.
[0084] The surface hyperbranched nano-silica is prepared by the following steps:
[0085] Step A: Add 1.5 parts by weight of nano-silica to 100 parts by weight of toluene, and then stir and mix at room temperature for 13 minutes in an ultrasonic wave with a power of 350 W, then add 1.3 parts by weight of epoxysilane, stir at 103° C. for 11 hours under a nitrogen atmosphere, filter, take the filter residue, wash it with acetone, and finally vacuum dry it at 60° C. until constant weight, to obtain epoxy nano-silica;
[0086] Step B: adding 2.5 parts by weight of epoxylated nano-silica to 100 parts by weight of 1,2-dichloroethane, and then stirring the mixture at room temperature for 13 minutes in an ultrasonic wave with a power of 350 W, and then dropping 18 parts by weight of a branched polyethyleneimine solution at 55° C. while stirring, and continuing to stir at a constant temperature for 5 hours after the dropwise addition is completed, filtering, taking the filter residue, washing it with anhydrous ethanol, and finally vacuum drying it at 50° C. until constant weight, to obtain amino hyperbranched nano-silica;
[0087] Step C: Add 2.5 parts by weight of amino hyperbranched nano-silica and 4.5 parts by weight of glycidyl methacrylate to 100 parts by weight of dimethyl sulfoxide, then stir in the dark at 70° C. for 5 h, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60° C. until constant weight, and the preparation is completed.
[0088] The epoxysilane in step A is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0089] The dropping rate in step B is controlled at 1.5 drops / s.
[0090] The branched polyethyleneimine solution in step B refers to a mixture obtained by mixing branched polyethyleneimine 600 and 1,2-dichloroethane in a mass ratio of 1:6 at 55° C. with stirring for 45 minutes and then maintaining a constant temperature.
[0091] The modified mineral powder is prepared by the following steps:
[0092] Step a: adding 7 parts by weight of deionized water, 2.5 parts by weight of mineral powder and 0.8 parts by weight of aminosilane to 100 parts by weight of anhydrous ethanol, stirring at 73° C. for 22 hours, filtering, taking the filter residue, washing with anhydrous ethanol, and finally vacuum drying at 60° C. until constant weight, to obtain an amination mineral powder;
[0093] Step b: Add 2.5 parts by weight of amination ore powder and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 75°C for 1.5 hours, filter, take the filter residue, wash it with N,N-dimethylformamide, and finally vacuum dry it at 103°C until constant weight, and the preparation is completed.
[0094] The aminosilane in step a is γ-aminopropyltrimethoxysilane.
[0095] A construction method for ultra-thin asphalt concrete, the construction method comprising the following steps:
[0096] Coarse aggregate, fine aggregate, modified mineral powder and basalt fiber were added to the modified asphalt, then stirred at 158°C for 25 minutes, spread on the road surface, cooled naturally to 93°C, rolled, and left to stand for 4 days.
[0097] The paving thickness is 2.3 cm.
[0098] The rolling refers to rolling using an 11T roller.
[0099] Comparative Example 1
[0100] On the basis of Example 1, the surface hyperbranched nano-silica was replaced with an equal weight of sulfur, and the rest remained unchanged.
[0101] Comparative Example 2
[0102] On the basis of Example 1, sulfur was replaced by surface hyperbranched nano-silicon dioxide of equal weight, and the rest remained unchanged.
[0103] Comparative Example 3
[0104] On the basis of Example 1, step A, step B and step C are not performed, the surface hyperbranched nano-silica is replaced with nano-silica of equal weight, and the rest remain unchanged.
[0105] Comparative Example 4
[0106] On the basis of Example 1, step B and step C were not performed, the epoxysilane in step A was replaced by an equal weight of vinyltrimethoxysilane, and the rest remained unchanged.
[0107] Comparative Example 5
[0108] On the basis of Example 1, step a and step b are not performed, the modified mineral powder is replaced with mineral powder of equal weight, and the rest remain unchanged.
[0109] Comparative Example 6
[0110] On the basis of Example 1, step a and step b are omitted, the modified mineral powder is replaced by the mineral powder of the same weight, the coarse aggregate is replaced by the modified coarse aggregate of the same weight, and the modified coarse aggregate is prepared by the following steps: step a: add 5 parts by weight of deionized water, 2 parts by weight of coarse aggregate and 0.5 parts by weight of γ-aminopropyltrimethoxysilane to 100 parts by weight of anhydrous ethanol, then stir at 70°C for 20 hours, filter by suction, take the filter residue, wash with anhydrous ethanol, and finally vacuum dry at 50°C until constant weight, to obtain amination coarse aggregate; step b: add 2 parts by weight of amination coarse aggregate and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 70°C for 1 hour, filter by suction, take the filter residue, wash with N,N-dimethylformamide, and finally vacuum dry at 100°C until constant weight, that is, the preparation is completed. The rest remain unchanged.
[0111] Comparative Example 7
[0112] On the basis of Example 1, step a and step b are omitted, the modified mineral powder is replaced by mineral powder of equal weight, the fine aggregate is replaced by modified fine aggregate of equal weight, and the modified fine aggregate is prepared by the following steps: step a: add 5 parts by weight of deionized water, 2 parts by weight of fine aggregate and 0.5 parts by weight of γ-aminopropyltrimethoxysilane to 100 parts by weight of anhydrous ethanol, then stir at 70°C for 20 hours, filter by suction, take the filter residue, wash with anhydrous ethanol, and finally vacuum dry at 50°C until constant weight, to obtain amino fine aggregate; step b: add 2 parts by weight of amino fine aggregate and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, then stir at 70°C for 1 hour, filter by suction, take the filter residue, wash with N,N-dimethylformamide, and finally vacuum dry at 100°C until constant weight, that is, the preparation is completed. The rest remain unchanged.
[0113] Test Example 1
[0114] Mechanical properties test:
[0115] The compressive strength test (coring method) was performed on the pavements after construction of Examples 1-3 and Comparative Examples 1-7 according to standard JTG 3450-2019 to illustrate the mechanical properties.
[0116] Table 4. Mechanical properties test results
[0117]
[0118] Comparison between Example 1 and Comparative Examples 1-7 shows that:
[0119] The difference between Comparative Example 1 and Example 1 is that the surface hyperbranched nano-silica in the composite auxiliary agent is replaced by an equal weight of sulfur.
[0120] The difference between Comparative Example 2 and Example 1 is that the sulfur in the composite auxiliary agent is replaced by an equal weight of surface hyperbranched nano-silicon dioxide.
[0121] The difference between Comparative Example 3 and Example 1 is that the surface hyperbranched nano-silicon dioxide in the composite auxiliary agent is replaced by nano-silicon dioxide of equal weight.
[0122] The difference between Comparative Example 4 and Example 1 is that the nano-silica does not form a surface hyperbranched structure, but the surface is still modified with double bonds.
[0123] The difference between Comparative Example 5 and Example 1 is that the modified mineral powder is replaced by mineral powder of equal weight.
[0124] The difference between Comparative Example 6 and Example 1 is that the mineral powder is not modified, but the coarse aggregate is modified in the same way.
[0125] The difference between Comparative Example 7 and Example 1 is that the mineral powder is not modified, but the fine aggregate is modified in the same way.
[0126] From the comparison between Example 1 and Comparative Examples 1-7 in Test Example 1, it can be seen that the ultra-thin asphalt concrete of the present invention can have more excellent mechanical properties after being actually constructed on the road surface.
[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An ultra-thin asphalt concrete, characterized in that: The ultra-thin asphalt concrete comprises 100 parts by weight of modified asphalt, 50-60 parts by weight of coarse aggregate, 20-25 parts by weight of fine aggregate, 15-20 parts by weight of modified mineral powder and 5-10 parts by weight of basalt fiber; The modified asphalt is prepared by the following steps: 100 parts by weight of base asphalt is heat treated at 165-170°C for 10-15 minutes, then 5-7 parts by weight of styrene-butadiene-styrene block copolymer is added, stirred at constant temperature for 20-30 minutes, then 2-3 parts by weight of composite additive is added, sheared at 175-180°C for 45-60 minutes, and finally grown at 160-165°C for 60-70 minutes, and the preparation is completed; the composite additive is a mixture of surface hyperbranched nano-silica and sulfur in a mass ratio of 1:0.3-0.4; The surface hyperbranched nano-silica is prepared by the following steps: Step A: Add 1-2 parts by weight of nano-silica to 100 parts by weight of toluene, and then stir and mix at room temperature for 10-15 minutes in an ultrasonic wave with a power of 300-400 W, then add 1-1.5 parts by weight of epoxy silane, stir at 100-105° C. for 10-12 hours under a nitrogen atmosphere, filter, take the filter residue, wash it with acetone, and finally vacuum dry it at 40-70° C. until constant weight, to obtain epoxy nano-silica; Step B: adding 2-3 parts by weight of epoxylated nano-silica to 100 parts by weight of 1,2-dichloroethane, and then stirring and mixing at room temperature for 10-15 minutes in an ultrasonic wave with a power of 300-400W, then adding dropwise 15-20 parts by weight of a branched polyethyleneimine solution at 50-60°C while stirring, and continuing to stir at a constant temperature for 4-6 hours after the dropwise addition is completed, filtering, taking the filter residue, washing it with anhydrous ethanol, and finally vacuum drying it at 40-70°C until constant weight, to obtain amino hyperbranched nano-silica; Step C: adding 2-3 parts by weight of amino hyperbranched nano-silica and 4-5 parts by weight of glycidyl methacrylate to 100 parts by weight of dimethyl sulfoxide, stirring for 4-6 hours at 60-80° C. in the dark, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 40-70° C. until constant weight, the preparation is completed; The modified mineral powder is prepared by the following steps: Step a: adding 5-8 parts by weight of deionized water, 2-3 parts by weight of mineral powder and 0.5-1 parts by weight of aminosilane to 100 parts by weight of anhydrous ethanol, stirring at 70-75° C. for 20-24 hours, filtering, taking the filter residue, washing it with anhydrous ethanol, and finally vacuum drying at 50-70° C. until constant weight, to obtain an amination mineral powder; Step b: adding 2-3 parts by weight of amination ore powder and 1 part by weight of diphenylmethane diisocyanate to 100 parts by weight of N,N-dimethylformamide, stirring at 70-80° C. for 1-2 hours, filtering, taking the filter residue, washing it with N,N-dimethylformamide, and finally vacuum drying at 100-105° C. until constant weight, and the preparation is completed; The epoxysilane in step A is 3-(2,3-epoxypropoxy)propyltrimethoxysilane; The branched polyethyleneimine solution in step B refers to a mixture obtained by mixing branched polyethyleneimine 600 and 1,2-dichloroethane in a mass ratio of 1:5-7 at 50-60° C. with stirring for 30-60 minutes and then maintaining a constant temperature.
2. The ultra-thin asphalt concrete according to claim 1, characterized in that: The shearing rotation speed is 4000-5000 rpm.
3. The ultra-thin asphalt concrete according to claim 1, characterized in that: The dripping rate in step B is controlled at 1-2 drops / s.
4. The ultra-thin asphalt concrete according to claim 1, characterized in that: The aminosilane in step a is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
Citation Information
Patent Citations
Ultrathin overlay modified asphalt and preparation method thereof
CN115505276A
Micro-overlay asphalt mixture and preparation method thereof
CN115710100A
Binding material for cold joint of asphalt pavement as well as preparation method and application of binding material
CN117925185A
Reacting nano inorganic particle / polymer composite material
CN1834147A